2020
DOI: 10.1038/s41380-020-0840-3
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic manipulation of an ascending arousal system tunes cortical broadband gamma power and reveals functional deficits relevant to schizophrenia

Abstract: Increases in broadband cortical electroencephalogram (EEG) power in the gamma band (30–80 Hz) range have been observed in schizophrenia patients and in mouse models of schizophrenia. They are also seen in humans and animals treated with the psychotomimetic agent ketamine. However, the mechanisms which can result in increased broadband gamma power and the pathophysiological implications for cognition and behavior are poorly understood. Here we report that tonic optogenetic manipulation of an ascending arousal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 80 publications
4
43
0
Order By: Relevance
“…Increased spontaneous broadband gamma oscillations have also been demonstrated in other mouse models of PV neuron dysfunctions (del Pino et al, 2013;Cho et al, 2015), and in individuals with schizophrenia (Mathalon and Sohal, 2015;Grent-'t-Jong et al, 2018). Further, administration of NMDAR antagonists such as ketamine (Pinault, 2008;Hakami et al, 2009;Kulikova et al, 2012;Caixeta et al, 2013;Picard et al, 2019;Lopes-Aguiar et al, 2020;Mahdavi et al, 2020;McNally et al, 2020), or MK-801 (Carlén et al, 2012;Molina et al, 2014;Hudson et al, 2020), is associated with increased power in spontaneous broadband gamma oscillations in both anesthetized and awake rodents, and also in humans (Rivolta et al, 2015). Importantly, lack of NMDAR in PV neurons blunts this response (Carlén et al, 2012;Picard et al, 2019;Hudson et al, 2020), confirming that cortical PV interneurons are a central target of NMDAR antagonists.…”
Section: Introductionmentioning
confidence: 97%
“…Increased spontaneous broadband gamma oscillations have also been demonstrated in other mouse models of PV neuron dysfunctions (del Pino et al, 2013;Cho et al, 2015), and in individuals with schizophrenia (Mathalon and Sohal, 2015;Grent-'t-Jong et al, 2018). Further, administration of NMDAR antagonists such as ketamine (Pinault, 2008;Hakami et al, 2009;Kulikova et al, 2012;Caixeta et al, 2013;Picard et al, 2019;Lopes-Aguiar et al, 2020;Mahdavi et al, 2020;McNally et al, 2020), or MK-801 (Carlén et al, 2012;Molina et al, 2014;Hudson et al, 2020), is associated with increased power in spontaneous broadband gamma oscillations in both anesthetized and awake rodents, and also in humans (Rivolta et al, 2015). Importantly, lack of NMDAR in PV neurons blunts this response (Carlén et al, 2012;Picard et al, 2019;Hudson et al, 2020), confirming that cortical PV interneurons are a central target of NMDAR antagonists.…”
Section: Introductionmentioning
confidence: 97%
“…However, the role of other neurochemically defined BF subtypes is unknown. Recent work has shown that one population of BF GABAergic neurons containing the calcium-binding protein parvalbumin (PV) control cortical fast oscillations and arousals from sleep [16][17][18][19] but their role in awake behavior is unclear. Thus, here we test the hypothesis that BF-PV neurons modulate vigilant attention in mice.…”
Section: Discussionmentioning
confidence: 99%
“…After establishing stable baseline performance (<10% change in mean session reaction time across three consecutive sessions), mice (N=6) were tested under each of three conditions: ChR2 (1s, 5mW continuous BF-PV excitation beginning 0.5s prior to cue light onset; Bilateral, brief and continuous low-wattage BF-PV excitation was used to enhance activity of BF-PV neurons without attempting to drive specific firing rate frequencies. Moreover, brief excitation closely timed to stimulus onset was used since prolonged (>30s) continuous BF-PV excitation disrupts performance in other tasks 18 .…”
Section: Excitation Of Bf-pv Neurons Enhances Vigilant Attention and Rescues Deficits Induced By Sleep Deprivationmentioning
confidence: 99%
“…EEG epochs were extracted around the investigation time, and gamma power (25-58Hz) was examined immediately after investigation onset vs a 4s "baseline" (0-4s pre-stimulus). This frequency range was selected because our preliminary data and previous studies [28] identified investigation-induced increases in 25-58Hz power, and this frequency range may signify top-down predictive coding in spatial working memory tasks [29]. Grand averages were taken across all epochs from all animals for each respective genotype after normalization.…”
Section: Social Task-elicited Gammamentioning
confidence: 99%